Improving the Competence of Electrical Power Installation Engineering Teachers in the Field of Smart Building Control Systems - Setyawan, Herlin; Habibullah; Risfendra; Sardi, Juli; Maulana, Ricky; Mulya, Rudi (Universitas Pendidikan Ganesha, 2025)
The problem addressed in this study is the mismatch between teachers’ existing competencies and the demands of the industry, particularly in smart building control systems, resulting in graduates lacking these essential skills. This study aims to enhance teachers’ professional competencies in smart building control systems through targeted training using smart building technology. A pre-experimental method was employed with one experimental class consisting of 16 teacher participants, using tests to assess knowledge and questionnaires to evaluate skills. The results were analyzed using paired-sample t-tests and effect size calculations, revealing significant improvements in both teachers’ knowledge and skills after the training. Furthermore, the large effect size indicates that the training had a substantial impact on enhancing competencies. These findings suggest that structured and precise training can effectively improve teachers’ knowledge and skills in emerging industrial technologies, which in turn positively influences the quality of education and increases graduates’ competitiveness in the labor market.